Analysis of the Implementation of the Occupational Safety and Health (K3) Program at the Madani Regional Hospital of Pekanbaru City in 2021 - Marzuki, Nurhidayati; Afandi, Dedi; Rahayu, Endang Purnawati (Budapest International Research and Critics University, 2021)
Occupational safety and health (K3) is a protective effort given to workers so that they are always in good health and provide safety in carrying out work activities and provide a sense of comfort to everyone who enters the workplace. The purpose of this study is to analyze the Implementation of of the implementation of the K3 program at the Madani Regional Hospital of Pekanbaru City in 2021. This study used a qualitative research method through in-depth interviews, observation and document review with 8 research informants, which were determined by purposive sampling. The results obtained are that the current human resources K3 of the Hospital are not sufficient, the infrastructure and K3 budget are inadequate, risk management has not been implemented, health services have not been carried out thoroughly, the management of toxic hazardous materials (B3) is not optimal, prevention and fire control and preparedness for emergency or disaster conditions have not been implemented because K3 officers also have responsibilities in other fields of work. The conclusion of this study is that the application of K3 at the Madani Regional Hospital of Pekanbaru City has not gone well. It is recommended to the hospital management to increase human resources K3 of the Hospital in accordance with the K3 educational background, complete the K3 facilities and infrastructure, allocate a special budget for the K3 program, carry out risk management, provide comprehensive occupational health services, carry out management according to standards, and carry out prevention and comprehensive fire and emergency control.